Prioritizing multifunctional conservation zones with dominant function based on comprehensive hotspots and bundles of ecosystem service - Liehui Zhi; Xiaowen Li; Junhong Bai; Dongdong Shao (Ecological Indicators)
Employing protected reserves is an effective approach to safeguard typical ecosystems and their biodiversity while overlooking intricate spatial interaction among multiple ecosystem services (ESs). This study attempts to establish an analytical framework that optimizes static conservation priority zones (CPZs) composed of ES hotspots integrating ecosystem service bundles (ESBs) and spatiotemporal trade-offs and synergies in multivariate ESs for realizing multifunctional collaboration. Focusing on the Yellow River Delta (YRD) from 1995 to 2020, we analyze three key ESs—water quality and carbon storage whilst incorporating biodiversity conservation. Our findings reveal significant protection gaps under a prescribed protection proportion within CPZs. Notably, two bundles in ESB trajectories by 2020, along with one bundle in the integrated ESB, resembled the CPZs under the 20% prescribed protection proportion in terms of distribution, area, and composition, with synergistic multivariate ESs markedly surpassing other zones. Regional optimization zoning under the synergy of multi-ESs was divided into four priority levels. This optimized zoning yields minimizing land use in the core priority zone, achieving 79% synergy with just 7% allocated for priority protection, thereby fostering efficient ecological safeguards. The ESB effectively optimizes static multifunctional CPZs through understanding spatiotemporal ES variations. This study enhances the understanding of efficient coastal ecosystem conservation and management in the YRD. The framework can support spatiotemporal multifunctional collaboration objectives and can also be extended to other regions.